VII. Chemical Constituents in the Surface Snow Cover in the Mizuho Plateau-West Enderby Land Area, East Antarctica, 1970-1971 - ムロズミ, マサヨ; シミズ, ヒロム; MUROZUMI, Masayo; SHIMIZU, Hiromu (National Institute of Polar Research, 1972)
P(論文) departmental bulletin paper